3D ULTRASOUND IN NORMAL AND CHANGES IN THE CERVIX - I. O. Makarov; T. V. Ovsyannikova; T. V. Shemanaeva; E. J. Borovkova; I. A. Kulikov; T. D. Guriev (IRBIS LLC, 2016)
This article describes the present views on ultrasound diagnosis of cervical changes. The generalized data on the size and measurement procedures. Pressing questions of the most common changes in the cervix.